Mother' involvement: children's perception of maternal childrearing practices - Hanafi, Zahyah (Universiti Utara Malaysia, 2004)
The purpose of this study is to identify maternal childrearing practices (achievement values, monitoring, and discussion) among employed and unemploved Malaysian mothers. Generally, these mothers have similar levels of childrearing practices. They instill high achievement values, conduct consistent monitoring on their children, and carry out regular discussions with them. They only differ in terms of monitoring. Discussion, implications, recommendations, and suggestions for future study are included.